A guide to organic electroreduction using sacrificial anodes. (2nd February 2023) - Li, Yufeng; Wen, Lirong; Guo, Weisi
Abstract : This review focuses on recent advances in sacrificial anode-enabled organic electroreductions. Abstract : Organic electrosynthesis is a green strategy for the synthesis of valuable molecules. Electrochemical reactions using sacrificial metal anodes enable new reactivity to be uncovered that could not be achieved with traditional non-electrochemical methods. Compared with reactions using metal powder as the reducing reagent, the mild electroreduction protocols usually exhibit diverse reactivity and excellent selectivity. The inexpensive metal anodes possess low oxidation potential, which could prevent undesired overoxidation of substrates, active intermediates and products. The in situ generated metal ions from sacrificial anodes could not only serve as Lewis acids to activate the reactants but also as a promoter or mediator. This tutorial review highlights the recent achievements in this rapidly growing area within the past five years. The sacrificial anode-enabled electroreductions are discussed according to the reaction type.